2022
DOI: 10.1021/acs.orglett.2c00938
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Conformational Switching of Amide Bonds─from Full trans to Full cis and Vice Versa

Abstract: Strategies enabling the pH-dependent conformational switching of amide bonds from trans to cis, and vice versa, are yet limited in the sense that, in a suitable pH range, one rotamer may be stabilized to a large extent while the complementary pH range only leads to a mixture of isomers. By exploiting the effects of steric demand and the interaction of the amide carbonyl with a positive charge, we herein present the first examples for reversible pH-dependent switching from full trans to full cis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Furthermore, the degrees of freedom left unconstrained by many classes of peptoid residue offer unexplored opportunities for designing flexible, switchable molecules. [74,75] 4.3.2 | How to design a peptoid structure…”
Section: R Groupmentioning
confidence: 99%
“…Furthermore, the degrees of freedom left unconstrained by many classes of peptoid residue offer unexplored opportunities for designing flexible, switchable molecules. [74,75] 4.3.2 | How to design a peptoid structure…”
Section: R Groupmentioning
confidence: 99%
“…Similarly, the geometries of the tertiary amide bonds in molecules such as peptoids depend on the substituents on the nitrogen atom. , In recent years, the conformational control of tertiary amide bonds of proline and peptoids was actively pursued, and the steric effect, n O → π* Ar interaction, carbonyl–carbonyl (CO···CO) n O → π CO * interaction, ,,, cooperative hydrogen bonding, and fluorine inductive effects were explored to stabilize one isomeric form over the other. In a recent study, the pH-dependent conformational switching of tertiary amide bonds was demonstrated by using one bulky and one pH-sensitive substituent on the amide nitrogen atom …”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the pH-dependent conformational switching of tertiary amide bonds was demonstrated by using one bulky and one pH-sensitive substituent on the amide nitrogen atom. 25 N,N′-diacylhydrazine (Figure 1A) is a small molecule drug scaffold that contains two adjacent amide bonds connected by a N−N single bond. The amide bond isomerization of N,N′diacylhydrazines can produce four different amide bond isomers [trans−trans (t−t), trans−cis (t−c), cis−trans (c−t), and cis−cis (c−c) (Figure 1C),].…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, an amide-type molecular switch with no appreciable minor peak was reported. 12 As a different approach, we envisioned that if this molecule is protonated in the crystalline state, this will be applicable to an on–off type molecular switch. In addition, the switch in the crystalline state would have its flexible nature reduced.…”
Section: Introductionmentioning
confidence: 99%